Pengaruh Infusa Biji Buah Pinang (Areca catechu) terhadap Tingkat Mortalitas Haemonchus Contortus pada Kambing Kacang - Mubarokah, Wida Wahidah; Makmun, Lutfan; Purwono, Edi; Cahyani, Annisa Putri; Pranatasari, Dewi; Akbarrizki, Muzizat; Awaludin, Aan (Jurnal Pengembangan Penyuluhan Pertanian, 2025)
Haemonchus contortus is the most pathogenic blood-sucking gastrointestinal nematode worm found in the abomasum of small ruminants, especially in goats and sheep. Haemonchus contortus has been identified as a significant problem in ruminants because it causes economic losses. The purpose of this study was to determine the effect of areca nut seed infusion (IBP) on the mortality rate of Haemoncus contortus. This study was divided into 9 groups, each group containing 10 Haemoncus contortus worms. Group I was treated with IBP 2.5%; group II was treated with IBP 5%; group III was treated with IBP 7.5%; group IV was treated with IBP 10%; group V was treated with IBP 12.5%; group VI was treated with IBP 15%; group VII was treated with IBP 17.5%, group VIII as a negative control (0.9% NaCl) and group IX as a positive control (Albendazole). Mortality of Haemonchus contortus was recorded every hour until the mortality of the worms was 100%. Data analysis with ANOVA, to determine the differences in the effects of different treatments, analysis of variance and significant differences (P <0.01) were carried out, followed by further testing by the Duncan method (Duncan Multiple Range Test). The results of this study indicate that IBP significantly affects the mortality rate of Haemonchus contortus at various concentrations. In this study, the best concentration to kill 100% Haemonchus contortus for 4 hours was IBP concentrations of 12.5% 15% and 17.5%